Nano formulation of Berberine (Brb): Transforming a natural alkaloid into advanced therapeutics - Anjali Chauhan, Rahul Gaur, Chandra Kanta (Journal of Applied Pharmaceutical Science, 2024)
A naturally occurring isoquinoline alkaloid “Berberine” (Brb) is found in various plant species of the genus Berberis, such as Berberis vulgaris, Berberis aristata, Berberis microphylla, and so on. This component has been studied extensively by various researchers and scientists for its diverse therapeutic properties, including anticancer, antiviral, antimicrobial antidiarrheal, and anti-inflammatory effects. One of the most remarkable applications of berberine is its efficacy in managing type-II diabetes, which is attributed to its capability to initiate adenosine monophosphate, glycolysis stimulation, protein kinases activation, inhibit mitochondrial function and thus collectively enhance the lipid and glucose metabolism. Also, Berberine has shown promising outcomes in addressing other health conditions, such as hypertension, cardiac arrhythmias, and congestive heart failure. In spite of its numerous benefits, extensive usage of berberine has been hindered by some challenges such as low bioavailability, limited absorption, and poor water solubility. Nano formulation has emerged as an auspicious approach to overcome these obstacles. This review highlights the advancements of using nano technology to overcome the limitations of berberine (Brb) associated with its absorption, dissolution, and bio-distribution, which are critical for its active application of pharmacology. While previous studies have explored the use of nano-carriers for transfer of drug, this review uniquely underlines an inclusive evaluation of several nanocarrier, together with lipid-based nanoparticles (SLNs, NLCs, micelles, and liposomes), polymeric-based nanoparticles (chitosan, alginate, dextran, and PLGA) and advanced materials (graphene, dendrimers, gold (Au), and silver (Ag) nanoparticles). It emphasizes their specific applications in treating conditions like diabetes, osteoarthritis, microbial infections, and melanoma, with special attention on innovative applications such as thermal therapy with AuNP-Brb and bio-imaging with Brb-based carbon dots. In conclusion, nanotechnology has shown an outstanding result in improving the therapeutic strength and delivery of berberine, more investigation is necessary to interpret these nanoparticle carriers into clinical applications. The detailing of specific therapeutic effects and this breadth of comparison highlight the novelty of this review, which sets a foundation for future research to translate these findings into clinical applications.
Keywords: Alkaloids, berberine (Brb), lipid, nanocarriers, nano-formulation, nanoparticles, therapeutic